Contemporary Review of Recent Literature on Intrusion Detection In IOT - M.Bhargav, Dr Yellamma Pachipala (International Journal of Advanced Science and Technology, 2020)
One of the leading technical progressions of computing is “Internet of Things” (IoT). The IoT carries in numerous services, promising individuals’ personal lives obtained from the reliable process. It is forecasted that by 2022 trillion IP objects (addresses) will be associated with the internet. Low accessibility and obscurity of many devices in the massive heterogeneous network makes it problematic to observe the flow of data. However, to protect networks, the intruders who are unauthorized should be identified within the limitations of each kind of device before distributing the system information. The concept of IoT is rapidly increasing into different industrial areas comprising automotive, logistics and healthcare.And IoT environment attains enormous prominence for ensuring security and safety of both connectivity and information. Contemporarily, the security of data is maintained via authenticating and encrypting mechanism. Nevertheless, the tools which are used for security cannot guarantee the complete protection in contrast to malevolent intruders.  Consequently, an efficient and appropriate Intrusion detection system (IDS) is obligatory for ensuring the security in the IoT. This paper endeavors to analyze diverse possible malware attacks and diverse detection methods available to prevent such kind of attacks.